Technical Advance: New in vitro method for assaying the migration of primary B cells using an endothelial monolayer as substrate. Issue 3 (21st June 2017) - Stewart‐Hutchinson, Phillip J.; Szasz, Taylor P.; Jaeger, Emily R.; Onken, Michael D.; Cooper, John A.; Morley, Sharon Celeste
Abstract : The use of activated endothelial cell monolayers as a substrate provides a novel method for analysis of primary B cell migration in vitro. Abstract : Migration of B cells supports their development and recruitment into functional niches. Therefore, defining factors that control B cell migration will lead to a better understanding of adaptive immunity. In vitro cell migration assays with B cells have been limited by poor adhesion of cells to glass coated with adhesion molecules. We have developed a technique using monolayers of endothelial cells as the substrate for B cell migration and used this technique to establish a robust in vitro assay for B cell migration. We use TNF‐α to up‐regulate surface expression of the adhesion molecule VCAM‐1 on endothelial cells. The ligand VLA‐4 is expressed on B cells, allowing them to interact with the endothelial monolayer and migrate on its surface. We tested our new method by examining the role of L‐plastin (LPL), an F‐actin‐bundling protein, in B cell migration. LPL‐deficient (LPL −/− ) B cells displayed decreased speed and increased arrest coefficient compared with wild‐type (WT) B cells, following chemokine stimulation. However, the confinement ratios for WT and LPL −/− B cells were similar. Thus, we demonstrate how the use of endothelial monolayers as a substrate will support future interrogation of molecular pathways essential to B cell migration.